Physiological responses to swimming repetitive "ice miles" - Knechtle, B.; Stjepanovic, M.; Knechtle, C.; Rosemann, T.; Sousa, C. V.; Nikolaidis, P. T. (The Journal of Strength and Conditioning Research, 2021)
"Ice Mile" swimming (i.e., 1,608 m in water of below 5° C) is becoming increasingly popular. Since the foundation of the International Ice Swimming Association (IISA) in 2009, official races are held as World Cup Races and World Championships. Ice swimming was a demonstration sport at the 2014 Winter Olympics in Sochi, Russia. This case study aimed to identify core body temperature and selected hematological and biochemical parameters before and after repeated "Ice Miles." An experienced ice swimmer completed 6 consecutive Ice Miles within 2 days. Three Ice Miles adhered to the strict criteria for the definition of Ice Miles, whereas the other 3 were very close (i.e., 5.2, 6.1, and 6.6° C) to the temperature limit. Swimming times, changes in core body temperatures, and selected urinary and hematological parameters were recorded. The athlete showed after each Ice Mile a metabolic acidosis (i.e., an increase in lactate and TCO2; a decrease in base excess and HCO3-) and an increase in blood glucose, cortisol, and creatine kinase concentration. The decrease in pH correlated significantly and negatively with the increase in cortisol level, indicating that this intense exercise causes a metabolic stress. The change in core body temperature between start and finish was negatively associated with metabolic acidosis. The increase in creatine kinase suggests skeletal muscle damages due to shivering after an Ice Mile. For athletes and coaches, swimming in cold water during Ice Miles leads to a metabolic acidosis, which the swimmer tries to compensate with a respiratory response. Considering the increasing popularity of ice swimming, the findings have practical value for swimmers and practitioners (e.g., coaches, exercise physiologists, and physicians) working with them because our results provide a detailed description of acute physiological responses to repeated swimming in cold conditions. These findings are of importance for athletes and coaches for National Championships and World Championships in Ice Swimming following the IISA rules.